HIV Stigma and Discrimination Management in Pokhara, Nepal - Aryal, Ram Prasad (Janapriya Journal of Interdisciplinary Studies, 2018)
Stigma and discrimination attached to Human Immuno-deficiency Virus (HIV) and Acquired Immuno-deficiency Syndrome (AIDS) are not new issues in Nepal where the issues are often considered to be the outcomes of either extra-marital sexual activities or sharing needles for drug use withpeople living with HIV (PLHIV). These activities are considered to be outside norms and values of Nepalese societies. Consequently, PLHIV are stigmatized and discriminated against in family and society. There are number of studies on stigma and discrimination attached to HIV and AIDS. However, there are very limited studies on management of HIV stigma and discrimination in Nepal. Therefore, this paper aims to look at HIV stigma and discrimination in general with a view to contextualize these issues, and to examine management of HIV stigma and discrimination in particular after being HIV diagnosed. This study follows qualitative research approach, face to face in-depth interview with 16 PLHIV in Pokhara during the period February-March 2017. This study investigates ways the participants have been able to manage their HIV stigma and discrimination in a greater extent at present with their own individual rigorous efforts, and supports made by local body and organizations/hospitals working in the field of HIV and AIDS as well. This paper has important policy implications, especially in the management of HIV stigma and discrimination in Nepal and other countries with similar socio-cultural contexts. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), page: 97-109